The determinant factors of biophilic design strategies and occupants' psychological performance in office building / Asniza Hamimi Abdul Tharim ... [et al.] - Abdul Tharim, Asniza Hamimi; Che Ahmad, Asmalia; Saarani, Puteri Sidrotul Nabihah; Raffikhul Haossain, Nur Qamarina; Purwanto, Edi; Ismail Tafridj, Issa Samichat; Purisari, Rahma; Prasetio, Teguh (Universiti Teknologi MARA, Perak, 2022)
Urbanization can result in the changing of climate change, global warming, threatens biodiversity, and decrease access to the natural environment. Hence the current lifestyle and urban living make people distance themselves from the natural world, especially during working hours. Therefore, biophilic design strategies function to eradicate the void between modern design, urbanization, and human needs. This paper is a review of the literature to investigate the predictors for biophilic design strategies in office buildings. It also examines the occupants' perceived psychological performance as the dependent variables for this study. Hence this paper aims to review previous literature related to biophilic in office buildings. This paper concludes that the three main predictors for biophilic strategies are: direct experience of nature; indirect experience of nature and experience of space and place. As for the dependent variables of this study, the Literature Review analysis concludes that there are five main outcomes related to occupants' perceived psychological performance in office building namely productivity, emotions, cognitive functions, reduce stress as well as the well-being of the occupants. A conceptual framework was developed based on the research variables that are to be tested later in green-rated office buildings in Malaysia and Indonesia. It is hoped that this research will bring benefits for biophilic implementation in both countries.